Many ways to TOPLESS – manipulation of plant auxin signalling by a cluster of fungal effectors. Issue 4 (9th August 2022) - Bindics, Janos; Khan, Mamoona; Uhse, Simon; Kogelmann, Benjamin; Baggely, Laura; Reumann, Daniel; Ingole, Kishor D.; Stirnberg, Alexandra; Rybecky, Anna; Darino, Martin; Navarrete, Fernando; Doehlemann, Gunther; et al.
Summary: Plant biotrophic pathogens employ secreted molecules, called effectors, to suppress the host immune system and redirect the host's metabolism and development in their favour. Putative effectors of the gall‐inducing maize pathogenic fungus Ustilago maydis were analysed for their ability to induce auxin signalling in plants. Using genetic, biochemical, cell‐biological, and bioinformatic approaches we functionally elucidate a set of five, genetically linked effectors, called Topless (TPL) interacting protein (Tips) effectors that induce auxin signalling. We show that Tips induce auxin signalling by interfering with central corepressors of the TPL family. CRISPR‐Cas9 mutants and deletion strain analysis indicate that the auxin signalling inducing subcluster effectors plays a redundant role in virulence. Although none of the Tips seem to have a conserved interaction motif, four of them bind solely to the N‐terminal TPL domain and, for Tip1 and Tip4, we demonstrate direct competition with auxin/indole‐3‐acetic acid transcriptional repressors for their binding to TPL class of corepressors. Our findings reveal that TPL proteins, key regulators of growth–defence antagonism, are a major target of the U. maydis effectome.